2009
DOI: 10.1103/physrevb.80.115209
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of pseudobinary GeTe,Ge2Sb2Te5,

Abstract: Fe doped GST has shown experimentally the ability to alter its magnetic properties by phase change. In this work, we use screened exchange hybrid functional to study the single neutral substitutional 3d transition metal (TM) in crystalline GeTe and GeSb2Te4. By curing the problem of local density functional (LDA) such as over delocalization of the 3d states, we find that Fe on Ge/Sb site has its majority d states fully occupied while its minority d states are empty, which is different than previous predicted e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
34
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(47 citation statements)
references
References 55 publications
12
34
1
Order By: Relevance
“…3). Our band-gap value is half of that measured experimentally (0.55 eV) [32]. We find that this forbidden gap is direct and located on the high-symmetry line Z-, where Z is located at the top of the Brillouin zone [see Fig.…”
Section: (Gete) 1 (Sb 2 Te 3 ) (Gst124)supporting
confidence: 54%
“…3). Our band-gap value is half of that measured experimentally (0.55 eV) [32]. We find that this forbidden gap is direct and located on the high-symmetry line Z-, where Z is located at the top of the Brillouin zone [see Fig.…”
Section: (Gete) 1 (Sb 2 Te 3 ) (Gst124)supporting
confidence: 54%
“…Previous tunneling spectroscopy [38] and concentration dependence of susceptibility mass study [39] suggested a smaller energy gap around 0.1-0.2 eV. The lowest band gap energy values of 0.8 eV for the amorphous GeTe by the extrapolation method [37] and tunneling spectroscopy [40] agreed with each other. Note that o-GeTe is proposed as a lower symmetry crystalline approximation to the real amorphous GeTe and its sX band gap coincides with the experimental value.…”
Section: Resultssupporting
confidence: 72%
“…Different experimental lowest band gap energy values have been reported for r-GeTe. Park et al [37] found this value to be 0.61 eV by linear extrapolation of the adsorption coefficient. Previous tunneling spectroscopy [38] and concentration dependence of susceptibility mass study [39] suggested a smaller energy gap around 0.1-0.2 eV.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations